Respuesta :
Answer:
Option: a is the correct answer.
(a) 1
Step-by-step explanation:
- Let the input of Feynman be denoted by i and it's output be denoted by f.
Now, it is given that:
Feynman, produces output, that is 5 times its input followed by an increase of 2.
i.e. the equation that will be formed using this information is:
[tex]f=5i+2------------(1)[/tex]
- Also, it is given that:
The output of Feynman feeds into Maxwell.
Let the output of Maxwell be denoted by m and it's input is f.
Maxwell, produces output, that is 5 times its input followed by a decrease of 2.
This means that the equation that will be formed using this information is:
[tex]m=5f-2----------------(2)[/tex]
Now, we put the value of f from equation (1) into equation (2)
i.e.
[tex]m=5(5i+2)-2\\\\i.e.\\\\m=25i+10-2\\\\i.e.\\\\m=25i+8[/tex]
If the output of Maxwell is: 33
i.e.
[tex]m=33[/tex]
Then
[tex]33=25i+8\\\\i.e.\\\\25i=33-8\\\\i.e.\\\\25i=25\\\\i.e.\\\\i=\dfrac{25}{25}\\\\i.e.\\\\i=1[/tex]
Hence, the input of Feynman is: 1